(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the basic methods and means of Education used in the Organization of the geography educational process, as well as their importance in improving the cognitive skills and abilities of students. All means of Education will be aimed at the successful implementation of educational goals. Educational tools are selected depending on the goals, contents, organizational forms and methods of geography education. The teacher can use instructional materials and training manuals at his discretion. Another aspect of the use of educational tools is that they appear as a component of the educational process. The didactic value of educational tools is to accelerate the assimilation of educational information. Choosing a particular educational tool is related to choosing a particular educational method. If an active method of education (working with books, exercises) is chosen, then training manuals, textbooks and technical tools are used. The classification of educational tools cannot be clear, uniform and unchanging. The importance of educational tools is that they are used together and never mutually exclusive.